Study on the heterosis for yield and yield contributing traits in sesame (Sesamum indicum L.) - P. L. Tavadare*, A. M. Misal, R. G. Gawali and A. R. Talape (Electronic Journal of Plant Breeding, 2022)
The present investigation was undertaken with an objective to study the magnitude of heterosis involved in 32 hybrids obtained by crossing four (female) x eight (male) genotypes in L x T fashion along with their 12 parents and two standard checks (JLT-408 and PRACHI) evaluated during summer, 2019-20 at Oilseeds Research Station, Latur. Data were recorded on yield and its different contributing traits. The analysis of variance for experimental design revealed significance differences among the parents, hybrids and parents vs hybrids for most of the characters indicated the presence of genetic variability among the experimental material. The crosses viz., SWETHA x V-25, V-34 x TBS-12, V-32 x TBS-7, SWETHA x R-26 and SWETHA x TBS-12 found with high heterobeltiosis and standard heterosis over check JLT-408 and PRACHI for seed yield along with other yield contributing traits. Significant heterobeltiosis and standard heterosis for seed yield were observed for the majority of yield and yield attributing traits. Selection of high heterotic hybrids with high per se performance would be reliable in the improvement of sesame.